Electricity Generation form Pretreated Palm Oil Mill Effluent Using Klebsiella Variicola as an Inoculum in Microbial Fuel Cell - Islam, Md. Amirul; Khan, Maksudur R.; Yousuf, Abu; Woon, Chee Wai; Cheng, C. K. (IEEE, 2016)
In this study, generation of electricity from pretreated palm oil mill effluent (POME) using Klebsiella variicola was investigated. POME wastewater with a COD value 68,360 mg/l was subjected to pretreatment with ultrasonication and used as a substrate. MFCs (Microbial Fuel Cell), enriched with pretreated palm oil mill effluent (POME) were subjected to generate electricity by using inoculation of K. variicola, collected from city wastewater. K. Variicola was isolated from city wastewater as well as from biofilm of MFC and identified using BIOLOG gene III analysis. The electrochemical activity and the performance of the MFC were evaluated by polarization curve measurement. The MFC showed average power density of 1648.70 mW/m3 and 1280.56 mW/m3 were obtained from ultrasonication pretrated POME and untreated POME respectively. The COD removal efficiency by K. variicola for POME with pretreatment was 74% and that for untreated was 48%. These results showed that the power output and COD removal efficiency can be raised in significant amount using pretreated POME in MFC.